Theorizing the Digital Object1 - Faulkner, Philip; Runde, Jochen (MIS Quarterly, 2019)
Prompted by perceived shortcomings of prevailing conceptualizations of digital technology in IS, we propose a theory aimed at capturing both the ontological complexity of digital objects qua objects, and how their identity and use is bound up with various social associations. We begin with what it is to be an object, the differences between material and nonmaterial objects, and various categories of nonmaterial objects including syntactic objects and bitstrings. Building on these categories we develop a conception of digital objects and a novel “bearer” theory of how material and nonmaterial objects combine. The role of computation is considered, and how the identity and system functions of digital objects flow from their social positioning in the communities in which they arise. Various implications of the theory are identified, focusing on its use as a conceptual frame through which to view digital phenomena, and its potential to inform existing perspectives with regard both to how digital technology per se and the relationship between people and digital technology should be theorized. These implications are illustrated with reference to secondary markets for software, the treatment of digital resources in the resource-based, knowledge-based, and service-dominant logic views of organizing, and recent work on sociomateriality.